Granisetron-mediated augmentation of sertraline therapeutic effect in obsessive-compulsive disorder: a double-blind placebo-controlled, randomized clinical trial - Ala Ghobadian; Saba Mokhtari; Behnam Shariati; Leila Kamalzadeh; Mohsen Shati; Mehrdad Eftekhar Ardebili; Masoomeh Yarahmadi; Mohammadreza Shalbafan (BMC, 2022)
Abstract Background Medications currently recommended for the treatment of Obsessive-Compulsive Disorder (OCD) usually relieve the severity of symptoms by as much as 20-30%, and satisfactory treatment is obtained in 40-60% of patients with OCD. Nevertheless, the remaining symptoms continue to impair the patients' function. Therefore, it is necessary to investigate possible strategies to improve the mitigation of symptoms. In this study, the main objective was to examine and investigate the effectiveness of granisetron, which is a serotonin 5-hydroxytryptamine receptor type 3 (5-HT3) antagonist, as an adjunct therapy to selective serotonin reuptake inhibitors, for the purpose of ameliorating OCD symptoms. Methods fifty-eight patients diagnosed with OCD, based on Diagnostic and Statistical Manual of Mental Disorders (DSM-5) criteria, who had a Yale-Brown obsessive-compulsive scale (Y-BOCS) score of more than 21 were recruited in a double-blinded, parallel-group, placebo-controlled, clinical trial of 10 weeks to receive either granisetron (1 mg twice daily) and sertraline (100 mg daily initially followed by 200 mg daily after week 4) or placebo and sertraline. The primary outcome was OCD symptoms measured by the Y-BOCS. Results Y-BOCS total score significantly dropped in both groups (28.9 to 17.7 for granisetron plus sertraline and 27.5 to 19.3 for placebo plus sertraline group with a slightly greater drop for granisetron plus sertraline group), while the granisetron plus sertraline group experienced a significantly greater reduction in obsession scores (Greenhouse-Geisser F(2.32,97.57) = 4.52,p-value = 0.01). Moreover, in comparison with the placebo plus sertraline group, the proportion of the patients showing complete response was considerably higher among the granisetron plus sertraline group (P-value < 0.01). No major adverse effects were observed in any of the groups. Conclusion The results suggest that granisetron augmentation of sertraline may increase the rate of response in patients with moderate to severe non-refractory OCD. Further studies are suggested in this regard.